The Role of Economic Diplomacy in Enhancing National Competitiveness - Czarnecka-Gallas, Marta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2012)
The paper aims at presenting the issues of economic diplomacy from economic perspective within competitiveness framework. The author combines two separately existing in the literature theoretical frameworks in order to obtain a new model of economic diplomacy. In the paper the thesis stating that economic diplomacy has been underused and limited only to macroeconomic factors of national competitiveness is discussed. The postulate of economic diplomacy to operate in close relations to micro factors of national competitiveness in order to contribute to country’s higher competitive position is proposed. Theoretical concept presented may serve both academics and policy makers as the reference point in their analysis, further empirical research and diplomatic strategy building. The novelty of the approach presented is competitiveness related model of economic diplomacy applied on both macro and micro-economic levels.

Celem artykułu jest ukazanie roli dyplomacji ekonomicznej we wzroście konkurencyjności danego państwa. Autor prezentuje model dyplomacji ekonomicznej w oparciu o teorię konkurencyjności, sankcjonując jej stosowanie w świetle argumentów ekonomicznych. Wysunięta teza twierdzi, że do tej pory termin „dyplomacja ekonomiczna” był odnoszony jedynie do makroekonomicznych czynników konkurencyjności. Tymczasem korzystanie z instrumentów dyplomacji ekonomicznej na poziomie mikroekonomicznym pozwoli na podniesienie konkurencyjnej pozycji kraju w sposób efektywny i zgodny ze współczesnym paradygmatem wzrostu gospodarczego.